Distrmution Range Extension of Bush Hopper Butterfly, Ampittia dioscorides Fabricius (Lepidoptera: Hesperiidae) into the Lower Western Himalayas - Singh, Arun P.; Bhandari, R. S. (Indian Forester, 2003)
No abstract